Framing Analysis of Raja Ampat Nickel Mine News on Indonesian Online Media - Tafuzi Fauriana; Guruh Ramdani (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
Online media play an important role in shaping public understanding of environmental issues through news framing. The issue of nickel mining in Raja Ampat has attracted public attention because the area is known as a conservation region with high biodiversity value. This study aims to analyze how Mongabay.co.id and Kompas.com construct reality regarding the conflict between ecological interests and natural resource industrialization in Raja Ampat. This study uses a qualitative approach with Zhongdang Pan and Gerald M. Kosicki’s framing analysis. The data consist of news articles related to nickel mining activities in Raja Ampat published by Mongabay.co.id and Kompas.com. The analysis focuses on syntactic, script, thematic, and rhetorical structures. The results show that Mongabay.co.id emphasizes environmental damage and ecological crisis through evaluative language and dominant environmental perspectives. Meanwhile, Kompas.com presents the issue in a more balanced and contextual way by combining social, policy, and governmental perspectives. The study concludes that differences in media framing influence public understanding of environmental damage, ecological crisis urgency, and the position of Raja Ampat as a conservation area.